Security of Tenure for Generation Rent: Irish and Scottish Approaches - Bennett, Mark (Victoria University of Wellington Law Review, 2016)
As fewer people are able to make the transition into home ownership, more New Zealand households do not have adequate security of tenure due to the lack of durational protections in the Residential Tenancies Act 1986. This article shows that Ireland and Scotland are comparable jurisdictions that have moved to regimes providing durational protections to residential tenants, allowing them to choose to remain in their home for a specified number of years or indefinitely, subject to a limited set of grounds for which the landlord may terminate the tenancy. We should consider these examples and take steps to provide greater durational protections, so that more New Zealanders may have homes that provide them with stable foundations on which they may build their lives.